2016
DOI: 10.1002/lt.24451
|View full text |Cite
|
Sign up to set email alerts
|

Development of a normothermic extracorporeal liver perfusion system toward improving viability and function of human extended criteria donor livers

Abstract: Donor organ shortages have led to an increased interest in finding new approaches to recover organs from extended criteria donors (ECD). Normothermic extracorporeal liver perfusion (NELP) has been proposed as a superior preservation method to reduce ischemia/reperfusion injury (IRI), precondition suboptimal grafts, and treat ECD livers so that they can be successfully used for transplantation. The aim of this study was to investigate the beneficial effects of a modified NELP circuit on discarded human livers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 41 publications
4
92
0
Order By: Relevance
“…Banan et al . have reported results from two human livers which were preserved normothermically with the addition of de‐fatting agents, namely l‐carnitine and exendin‐4. However, in the two treated livers, only one showed a minimal reduction in the degree of macrovesicular steatosis (10%) after 8 h NMP .…”
Section: Perfusion and Re‐conditioning Methods For Abdominal Organsmentioning
confidence: 99%
“…Banan et al . have reported results from two human livers which were preserved normothermically with the addition of de‐fatting agents, namely l‐carnitine and exendin‐4. However, in the two treated livers, only one showed a minimal reduction in the degree of macrovesicular steatosis (10%) after 8 h NMP .…”
Section: Perfusion and Re‐conditioning Methods For Abdominal Organsmentioning
confidence: 99%
“…The need of plasma volume expansion may be due to suboptimal perfusion conditions in our experimental setup because it is not integrated to most of the clinically used systems. However, Banan et al used a dialyzer to maintain the perfusate pH and electrolyte profiles within physiologic ranges throughout the 8‐hour NEVLP of human liver grafts . Rigo et al recently reported on escalating transaminase release during 4 hours of normothermic perfusion of rat livers without dialysis, resulting in significant damage of the liver architecture …”
Section: Discussionmentioning
confidence: 99%
“…Additional to an osmotic effect, it has been shown that a high concentration of urea (100 mmol/L) negatively affects hepatic metabolism via proteolysis inhibition . For this reason, Banan et al incorporated a dialyzer to clear the urea and glucose in the circuit, but it would not be feasible in a portable system. Also, the costs of adding a dialyzer to the system will be $20,000–$30,000 …”
Section: Discussionmentioning
confidence: 99%